The Importance of Preparing Preschool Children for School Education - Meliboyeva Shokhistakhon Mukhiddinovna; Ganiyeva Dildorakhon Mukimovna (International Journal on Orange Technologies, 2021)
It is known that a child should reach a level of development that can meet the requirements of the educational institution, and only then send the child to school. possible. In this process, it is important to prepare the child for school education, which is why the article focuses on preschool children the importance of preparing for school education has been explored.